Review Of VAT Administration Based on The Core Tax Administration System (CTAS): A Case Study of The Surabaya Sukomanunggal Tax Office - Dewi Laras Ati; Asqolani Asqolani (IPSAR (International Public Sector Accounting Review), 2025)
This study aims to review the VAT administration mechanism in the early stages of CTAS implementation, analyze its advantages, and identify challenges faced. The research focuses on VAT administration through CTAS at the Surabaya Sukomanunggal Tax Office from January to June 2025. The DGT asserts that the digitalization of tax administration is an integral part of bureaucratic reform that cannot be postponed. However, some parties consider this system not yet fully ready due to challenges in infrastructure, human resource quality, and community readiness to adapt. The method used in this study is qualitative analysis. The results show that the implementation of CTAS in VAT administration is relatively practical because it integrates all administrative processes in a single web-based system. Nevertheless, various technical problems and policy misalignments remain as barriers to its optimal implementation. Therefore, the DGT needs to improve system stability and capacity, refine CTAS features according to taxpayer needs, and strengthen support through education and clear regulations.